Die Gesellschaft der Nachhaltigkeit -- Umrisse eines Forschungsprogramms - Hasenfratz, Martina (transcript Verlag, 2018)
Sustainability has become a leading principle of social change that combines different objectives - be it green capitalism based on ecological modernization or a socio-ecological transformation that could ring in a post-capitalist era. The social dimensions of sustainability as well as the paradoxes relating to a sustainable development in global capitalism are examined in this programmatic text by Sighard Neckel and his research team in Hamburg. Basic sociological perspectives of sustainability are the subject, as are prospects of concrete fields of a critical-reflexive social research on the social conflicts centering around sustainability.